Analysis Website Acceptance of Hotel Sahid Surabaya by using model of Unified Theory of Acceptance and Use of Technology (UTAUT) - Mohamad Ardan Ginanda; Sulistiowati Sulistiowati; Puspita Kartikasari (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2018)
Website Hotel Sahid Surabaya is a web company profile in which there are functions to support the process of e-commerce suite at Mission Hotel Sahid Surabaya. The e-commerce process will be more optimal if users use website usage. But in fact from the survey conducted involving 20 people to access the website, 17 people have difficulty choosing the view that will be accessed to make an online reservation so that respondents prefer to make a reservation directly because when making a reservation via the website there is no indication that it is difficult for a user in make a reservation. During its implementation, the Sahid Hotel Surabaya website has never been evaluated.The solution to this problem is to analyze the variables that affect the acceptance of the website by using the Unified Theory of Acceptance and Use of Technology (UTAUT) model. This model has 4 independent variables, 4 moderating variables and 2 dependent variables. To determine the effect between variables using Structural Equation Model, Partial Least Square. The sampling technique used Ferdinand's theory with 75 respondents.Based on the results of the analysis on the model (UTAUT), it can be known that the influential variables with the T-Statistic provisions ≥ 1.96 or Pvalue ≤ 0.05 are Behavioral Intention to Use Behavior of 40.1% and Social Influence to Behavioral Intention of 33%. Based on the mean value of the influential variables, it is in the interval class (2.50-3.24) which means the respondent agrees to the statement and recommendations produced, that is, the receptionist of Hotel Sahid Surabaya offers to use the website for reservations, because if someone feels satisfied using the website it will affect the user another to use it. As for the second recommendation all information must be included on the website. Keyword: SEM, SmartPLS, Unified Theory of Acceptance and Use of Technology (UTAUT),Website Hotel Sahid Surabaya